Match outcome and sprinting activities in match play by elite German soccer players - Andrzejewski, M.; Chmura, P.; Konefal, M.; Kowalczuk, E.; Chmura, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the study was to examine the ways playing positions and match outcome (i.e. win, draw, loss) affect the sprint distance covered and the number of sprints performed by German Bundesliga soccer players. METHODS: Match performance data were collected from 350 soccer players competing in the German Bundesliga during the 2014/2015 domestic season. A total of 4393 individual match observations were undertaken on outfield players. The analysis was carried using the Impire AG motion analysis system with records of all movements of players in all the 306 matches. The recorded variables included total sprint distance covered and the total number of sprints in offensive and defensive play. The conformity assessment was carried out with the Shapiro-Wilk test (P=0.01). To compare mean values of the examined variables a two-way ANOVA was used. The differences between pairs of means were verified with Fisher`s LSD. RESULTS: The analysis of the covered sprint distance and the number of performed sprints showed that central defenders and full-backs covered shorter distances in won matches than in lost matches (P=0.05). Furthermore, forwards and wide midfielders covered significantly longer sprint distances in won matches than in lost matches (P=0.05). CONCLUSIONS: The match outcome may be viewed as a measure of performance accomplishment and, hence, it may influence the sprinting efforts made by players.